Sources used and the challenges encountered by newspaper journalists when covering environmental conservation information in Tanzanian newspapers - Siyao, Peter Onauphoo; Mbughuni, Anna Shangwe; Chishami, Ashery Mhulula (Sage, 2025)
Background: Environmental conservation is a crucial global issue, and in Tanzania, newspaper journalists play a vital role in raising awareness and educating the public. Purpose: This study explores the sources Tanzanian newspaper journalists use to gather environmental conservation information and examines the challenges they face in reporting on these issues. Research Design, Study Sample, Data Collection and/or Analysis: Using a qualitative research design, the study involved journalists from four major newspapers: Daily News, The Guardian, Mwananchi, and Habari Leo. A purposive sampling technique was used to select 20 journalists for in-depth interviews and content analysis of published articles. Results: The findings indicate that journalists rely on sources such as government agencies, environmental conservation organizations, academic experts, community voices, social media, corporate sources, international reports, and their own observations to cover information they publish in the newspapers. However, they encounter barriers such as a lack of prioritization for environmental news, resource constraints, insufficientskills and knowledge, time limitations, low public literacy on environmental issues, restricted access to credible information, and political and commercial pressures. Conclusion: This study highlights the need for improved journalism education and policy support to enhance environmental reporting. It recommends comprehensive training for journalists, increased awareness of the importance of environmental news, better access to diverse sources, and a supportive media environment to strengthen conservation coverage in Tanzania.